(3Mb GdOaGY GdTQYi Hjf GdbGfhf GdLfGFi GdhVYi h GdTQjYI GdESdGejI (B/ s - (3CMeO MSf YHOGddg aQGLs; (3TQja cGeds; (3eMeO fLjH YhVjfs; (3LGeYI GdbGgQIs (3cdjI GdMbhbs ((3GdbGgQI (B: s (3cdjI GdMbhb(B-(3LGeYI GdbGgQI,s, 2013)
(3GdQSGdI JeKd HMKG ebGQfG Hjf Mb GdOaGY GdTQYi ai GdbGfhf GdhVYi h Hjf GdMb ai OaY GdUGFd ai GdTQjYI GdESdGejI(B: (3h Pdc dJbOjQ eOi GdGJaGb Ch GdENJdGa ai eLGd GdJTQjY dJhbjY GdYbGH Ch ESbGWg HEHGMI GdaYd(B. (3aCTGQ GdHMK Edi CSGS gPG GdMb h CQcGfg h TQhWg ef MjK VQhQI Cf jchf GdGYJOGA ZjQ eTQhY(B. (3h Cf jchf GdNWQ MGd Ch hTjc GdhbhY(B. (3h Cf jbY GdGYJOGA Ydi eWdb GdfaS Ch GdeGd ceG jTJQW ddOaGY Cf jchf dGReG eJfGSHG (B- (3ceG Hjf GdHMK GdBKGQ GdeJQJHI Ydi EHGMI GdaYd ceG CTGQ Edi MGdGJ GdJLGhR ai cd GdbGfhf h GdTQjYI(B: (3ceG CXgQ GdHMK SjGOI MGdI GdGJaGb abO CHOi GdQCi ajeG dGM ef THgGJ GdGNJdGa h bO GbJQM GdHMK eG QBg ef JYOjdGJ ai HYV ehGO GdbGfhfs
(3GWQhMI (B((3OcJhQGg(B) - (3LGeYI GdbGgQI (B- (3cdjI GdMbhb (B- (3bSe GdbGfhf GdLfGFj, (B2013s
(3HHdjhLQGajG(B: (3UaMGJ (B600-608s
(3GdedNU HGddZI GdYQHjIs
Keywords: (3GdbGfhf GdLfGFjs; (3fXQjI GdEcQGg GdeYfhis; (3fXQjI GdMb GdWHjYis; (3YhGQV GdEHGMIs; (3JYQja GdOaGY GdTQYis; (3GSGS GdOaGY GdTQYi s; (3GQcGf GdOaGY GdTQYis; (3TQhW GdNWQ s; (3Mb GdOaGY GdTQYis; (3TQhW GdEYJOGAs; (3GdOaGY Yf GdYQV ai GdTQjYI GdESdGejIs; (3JLGhR MOhO GdOaGY GdTQYis; (3QSGFd LGeYjIs -- (3LGeYI GdbGgQIs -- (3GdbGfhf GdLfGFjs